MOESLEM ABDURRAHMAN PEMIKIRAN TEOLOGI ISLAM TRASNFORMATIF - Agustina Damanik (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
The finding is that in Moeslim Abdurrahman's view, the paradigm of transformative theology is a theological view that departs from the issues of ignorance, backwardness and shortsightedness into modernist theologies that are adaptive to the progress of the times, offset by a critical attitude towards the negative elements of the modernization process. In other words, as a flexible, open and dialogical attitude in facing a plural and constantly changing world.